2021
DOI: 10.1021/acs.est.0c08731
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt-Promoted MgO Adsorbents for CO2 Capture: Transient Kinetic Studies

Abstract: Optimization of MgO adsorbents is predominantly focused on the regulation of appropriate adsorption sites for CO 2 associated with Mg 2+ -O 2− sites of low coordination. Here, for the first time, we conducted transient kinetic experiments to identify and characterize changes of the CO 2 molecular path in MgO-based CO 2 adsorbents upon the addition of molten salt modifiers. Among the optimized samples, addition of 10 mol % NaNO 2 on the surface of MgO exhibited the highest CO 2 uptake (15.7 mmol g −1 ) at 350 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 40 publications
(95 reference statements)
0
20
0
Order By: Relevance
“…This indicated the conversion of sodium nitrite to sodium nitrate, while MgO still remained in its pure bulk crystalline structure as also reported. [ 23 ] Detailed X‐ray photoelectron spectra of N 1s region confirmed that the surface was enriched with NaNO 2 /NaNO 3 species (Figure 1b). [ 26 ] The X‐ray photoelectron spectroscopy (XPS) spectrum of fresh NaNO 2 ‐promoted MgO sample depicted in Figure 1b shows a peak at 403.8 eV, which is attributed to the N 1s core level of NO 2 − .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This indicated the conversion of sodium nitrite to sodium nitrate, while MgO still remained in its pure bulk crystalline structure as also reported. [ 23 ] Detailed X‐ray photoelectron spectra of N 1s region confirmed that the surface was enriched with NaNO 2 /NaNO 3 species (Figure 1b). [ 26 ] The X‐ray photoelectron spectroscopy (XPS) spectrum of fresh NaNO 2 ‐promoted MgO sample depicted in Figure 1b shows a peak at 403.8 eV, which is attributed to the N 1s core level of NO 2 − .…”
Section: Resultsmentioning
confidence: 98%
“…The latter is due to the lower diffraction intensities derived from the various planes of NaNO 2 and its smaller amount (wt%) present in the sample. [23,28] Scanning electron microscopy (SEM) studies were further conducted on NaNO 2 -promoted MgO after activation, and typical adsorbent agglomerated particles are shown in Figure S1a, Supporting Information. Furthermore, energy-dispersive X-ray spectroscopy (EDS) analysis (N, O, Na, and Mg) indicated that the molten salt was evenly dispersed on the MgO surface (Figure S1b, Supporting Information).…”
Section: Structure and Surface Composition Of Molten-salt-promoted Mgomentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lower sorption temperatures of MgO compared to CaO, a popular approach to enhance the kinetics of CO 2 uptake of MgO is its promotion with alkali metal nitrates such as LiNO 3 , NaNO 3 , and KNO 3 . , Webley and co-workers , studied adsorbents based on double salts of MgCO 3 with either K 2 CO 3 or Na 2 CO 3 prepared by wet mixing; others investigated also Cs 2 CO 3 or Rb 2 CO 3 . , K–Mg double salts reached a CO 2 uptake of 8 wt % at 375 °C in pure CO 2 , while Na–Mg double salts showed higher CO 2 uptakes reaching between 15 wt % and ∼20.7 wt % . Zhang et al .…”
Section: Materials Optimizationmentioning
confidence: 99%
“…The overall kinetics of the CO 2 uptake by the molten salts with the nucleation and growth of the carbonate crystalline particles, which can eventually form diffusional barriers for further uptake can be qualitatively described by considering the time intervals over which the uptake rate changes separately. 12,45,46 The initial CO 2 uptake can be described by the pseudo firstorder reaction kinetics: 12,45…”
Section: Co 2 Absorption In Pressure Swing Cycling Operationmentioning
confidence: 99%